Single Parent Psychology Who Confirmed Positive Covid-19 - Padila, Padila; Andri, Juli; Sartika, Andry; Andrianto, Muhammad Bagus; J, Harsismanto (JOSING: Journal of Nursing and Health, 2021)
This study aims to explore the psychological experiences of single parents with confirmed COVID-19. The design of this study is a phenomenological approach because what is being studied is experience. The participants involved were single parents with confirmed COVID-19, with the instrument used as an in-depth interview guide related to their psychological experiences with confirmed COVID-19. The results of this study obtained five themes, namely the transmission of covid-19 occurs due to infection from friends in the work environment and after traveling, feelings when confirmed with covid-19, single parents experience shortness of breath, anxiety, worry, fear, shaking, insomnia, headaches, and anxiety. Was. In self-care, single parents ask to be cared for independently at home by taking medicines, vitamins, herbs to maintain progress and experience changes in excessive eating patterns. This he also applies to his children so that children stay healthy. The conclusion is that single parents experience psychological problems, namely anxiety, with a moderate level when confirmed positive for COVID-19. Keywords: Covid-19, Psychological, Single parent, Phenomenology